VGLL fusions define a new class of intraparenchymal central nervous system schwannoma - Schmid, Simone; Mirchia, Kanish; Tietze, Anna; Liu, Ilon; Siewert, Christin; Nückles, Jakob; Schittenhelm, Jens Florian; Behling, Felix; Snuderl, Matija; Hartmann, Christian; Brandner, Sebastian; Paine, Simon M L; et al. (Neuro-Oncology, 2025)
Intracerebral schwannomas are rare tumors resembling their peripheral nerve sheath counterparts but localized in the central nervous system (CNS). They are not classified as a separate tumor type in the 2021 World Health Organization classification. This study aimed to compile and characterize these rare neoplasms morphologically and molecularly.We analyzed 20 tumor samples by histology, RNA next-generation sequencing, DNA-methylation profiling, copy number analyses, and single-nucleus RNA sequencing (snRNA-seq). Clinical data, including age, sex, and disease progression, were collected. Magnetic resonance imaging (MRI) series were included when available.All cases with tissue available for histology review (n = 13) were morphologically consistent with intracerebral schwannoma, but differed in their extent of glial fibrillary acidic protein staining. All (n = 20) shared DNA-methylation profiles distinct from other CNS tumors, as well as from Vestigial-like family (VGLL)-altered peripheral nerve sheath tumors. Most cases (n = 14/17) harbored fusions of either Vestigial-like family member 3 (VGLL3) or Vestigial-like Family member 1 (VGLL1) (CHD7::VGLL3 [n = 9/17] and EWSR1::VGLL1 [n = 5/17]). In 2 cases, the presence of a VGLL3 fusion was also confirmed by copy number analyses (n = 2/17). MRI (n = 4) showed well-defined, nodular tumors with strong, homogeneous enhancement and no diffusion restriction. Tumors were located throughout the neuroaxis (supratentorial [n = 15], infratentorial [n = 4], and spinal [n = 1]). snRNA-seq of a VGLL1-fused tumor indicated VGLL1 upregulation in 28.6% of tumor cells (n = 1). During a median follow-up of 1.8 years (range 3 months-9 years), none of the tumors recurred (n = 10).We identify and define a new benign tumor class, designated VGLL-altered intraparenchymal CNS schwannomas. These tumors feature VGLL alterations and a specific DNA-methylation profile, with schwannoma-like histopathology and CNS localization, akin to previously classified intracerebral schwannomas.